Describing self‐care and its associated variables in ostomy patients. (26th August 2020) - Giordano, Vittoria; Nicolotti, Matilde; Corvese, Francesco; Vellone, Ercole; Alvaro, Rosaria; Villa, Giulia
Abstract: Aims: To describe self‐care in ostomy patients, to identify socio‐demographic and clinical variables associated with self‐care and to identify the association between self‐care self‐efficacy and self‐care over and above the variables associated with self‐care. Design: Longitudinal and multicentre study. Data were collected between February 2017‐May 2018. Methods: In this study, 523 ostomy patients were enrolled at baseline (T0) and 362 were followed‐up after 6 months (T1). The Ostomy Self‐Care Index was used to measure self‐care maintenance, monitoring, management, and self‐efficacy. Correlations between self‐care dimensions and patient socio‐demographic and clinical characteristics were performed with Pearson's or Spearman's correlations. Three separate two‐step hierarchical regression analyses were performed to identify variables associated with self‐care maintenance, monitoring, and management. Results: Participants' mean age was 69 years ( SD 12.4); 63.9% were male and most had enterostomies (38.8% colostomies, 29.3% ileostomies) and permanent ostomies (72.5%). Patients had adequate self‐care maintenance and monitoring at T0 and T1, while they had lower self‐care management and self‐efficacy at baseline. Significant variables associated with better self‐care maintenance and self‐care monitoring were female gender, more information received during hospitalization and better autonomy in stoma management, while a better level of education was an additional variable associated with self‐care monitoring. Self‐care self‐efficacy produced a significant increase in the explained variance of self‐care maintenance and self‐care monitoring. None of the selected variables were significantly associated with self‐care management. Conclusion: Middle‐high levels of self‐care maintenance, monitoring, management, and self‐efficacy were found. The variables associated with ostomy self‐care and the role of self‐care self‐efficacy identified in this study can help in developing tailored nursing interventions. Impact: This study found specific variables associated with ostomy self‐care which could contribute to guiding future interventions aimed at improving self‐care in ostomy patients. 摘要: 目标: 描述造口术患者的自我护理, 识别与自我护理相关的社会人口统计学和临床变量, 并确定自我护理自我效能感和自我护理之外与自我护理相关变量之间的关系。 设计: 纵向研究和多中心研究。数据收集时间为2017年2月至2018年5月。 方法: 在这项研究中, 基线位置(T0)招募了523名造口术患者, 之后6个月(T1)对362名患者进行随访。使用造口术的自我护理指数衡量自我护理的维持、监测、管理和自我效能感。采用皮尔逊或斯皮尔曼相关理论分析自我护理维度与患者社会人口统计学和临床特征之间的相关性。进行了三个独立的两步分层回归分析, 确定与自我护理维护、监测和管理相关的变量。 结果: 受试者的平均年龄为69岁(标准差12.4);63.9%为男性, 大多数接受过肠造口术(38.8%为结肠造口术, 29.3%为回肠造口术)和永久造口术(72.5%)。患者在T0和T1位置进行了充分的自我护理维持和监测, 但在基线位置时, 其自我护理管理和自我效能感均偏低。与优质的自我护理维护和自我护理监测相关的重要变量是女性、在住院期间获得更多信息、在造口管理中拥有更好的自主权, 并且受过更好的教育是与自我护理监测相关的另一个变量。自我护理的自我效能感显著提高了自我护理维护和自我护理监测的可释方差。选定变量均与自我护理管理无显著相关。 结论: 得出自我护理维护、监测、管理和自我效能感处于中高水准。本研究中确定的与造口术自我护理相关的变量和自我护理自我效能感的作用有助于制定定制化的护理干预措施。 影响: 该研究发现与造口术自我护理相关的具体变量有助于指导未来旨在改善造口术患者自我护理的干预措施。